Enhancing English Language Learning in Tertiary Education through Blended Approaches: A Bangladesh Perspective - Rabbi, Md. Fajlay; Islam, Md. Sefatul; Hossain, Md. Jamil (Indonesian Journal of Educational Studies, 2023)
The modern educational landscape is witnessing a paradigm shift with the integration of technology into traditional teaching methods. Blended learning, a pedagogical approach combining face-to-face instruction with online resources, holds the potential to revolutionize English language learning in Bangladesh's tertiary education system. This paper explores the significance, benefits, challenges, and strategies of employing blended learning within the context of English language education in Bangladesh. By harnessing the advantages of both in-person and online components, blended learning offers flexible access, heightened engagement, and personalized learning experiences. This study investigates the implications of adopting blended approaches in enhancing English language proficiency, bridging the digital divide, and preparing students for the demands of a globalized world. Through a Bangladesh perspective, this research seeks to illuminate the transformative power of blended learning in shaping the future of English language education in tertiary institutions.